Formulation and Evaluation of a Combined Chloroquine Phosphate and Chlorpheniramine Maleate Product (Journal of Science and Technology, 2016)
Chloroquine phosphate granules (B1) and chlorpheniramine maleate granules (B2) were separately formulated with maize starch and lactose with polyvinylpyrrolidone (10% w/v) as binder. B1 was coated with 5% w/v ethylcellulose to varying degrees by increasing the spray time of the coating solution by 2 minutes between successive batches to produce B1A, B1B, B1C, B1D, B1E, B1F, B1G, B1H and B1I of increasing coat thickness. B2 was not coated. The release profiles of the coated and uncoated granules were studied using the US Pharmacopoeia XXIV (2000) dissolution apparatus II. The release profiles showed a significant and progressive retardation of the release of chloroquine phosphate from B1A to B1I as the coating time was increased. Batch B1I which gave the most desired release profile was selected and combined with the chlorpheniramine maleate granules, encapsulated and the release profiles studied. Each capsule contained granules equivalent to 4mg chlorpheniramine maleate (uncoated) and 250mg chloroquine phosphate (coated). Almost all the chlorpheniramine (97.4%) in the combined product (capsule) was released in 35 min while only about a quarter (24.4%) of the chloroquine component was released in the same period. The combined formulation appears to possess the ability to protect susceptible patients from chloroquine-induced itching by releasing a greater amount of the antihistamine before the chloroquine is released.